Effects of Antecedent Exercise on Academic Engagement and Stereotypy During Instruction. (January 2015) - Neely, Leslie; Rispoli, Mandy; Gerow, Stephanie; Ninci, Jennifer
Antecedent physical exercise has emerged as a potentially promising treatment for reducing challenging behavior and increasing academic behavior in individuals with autism spectrum disorder (ASD). The purpose of this study was to evaluate the effects of physical exercise conducted prior to instructional sessions (antecedent physical exercise) on academic engagement and stereotypy during instructional sessions for two children diagnosed with ASD. Functional analysis results suggested stereotypy was maintained by automatic reinforcement for both participants. A multielement design was employed to evaluate academic engagement and stereotypy during instructional sessions following randomly sequenced conditions involving either (a) no antecedent exercise, (b) brief durations of antecedent exercise, or (c) antecedent exercise that continued until the participant engaged in a systematically determined behavioral indicator of satiation. Both participants demonstrated higher levels of academic engagement and reduced levels of stereotypy during the instructional sessions which followed antecedent physical exercise that continued until behavioral indicators of satiation occurred. This study replicates previous research suggesting that individuals with ASD may benefit from physical exercise prior to academic instruction and further suggests that the duration of antecedent exercise may be optimally individualized based on behavioral indicators of satiation.